Review of Invertebrate Biological Control Agents Introduced into Europe. - Gerber, Esther. (CAB International, 2016)
This book provides an overview of all documented releases of exotic (non-European) invertebrate biological control agents (IBCAs) into the environment in Europe and summarizes key information on the target species as well as on the biological control agent released.